Body weight‐based initial dosing of tacrolimus in renal transplantation: Is this an ideal approach?. Issue 1 (30th July 2020) - Chinnadurai, Rajkumar; Ibrahim, Sara T.; Tay, Tricia; Bhutani, Shiv; Kalra, Philip A.
Abstract: Background: Tacrolimus dosing immediately posttransplant is based on body weight. Recent studies have highlighted that the dosing of tacrolimus purely based on weight may not be appropriate, particularly in individuals who are obese. Objectives: This study aimed to estimate the effect of body mass index (BMI) and the weight‐based dosing on tacrolimus trough levels in recipients of renal transplants. Design and Participants: This study was conducted on 400 of the 863 patients registered in the Salford, UK, renal transplant database between 2012 and 2019 who had complete and analysable datasets. Data were collected at baseline (first tacrolimus trough level after transplantation), after 1 month and 6 months posttransplantation. The cohort was split into three groups based on BMI (kg/m 2 ; Group 1 ≤ 25, Group 2 > 25–30 and Group 3 > 30) which were compared with respect to tacrolimus dose, plasma levels and concentration/dose (C/D) ratio at the three‐time points. Results: Patients in the higher BMI group (Group 3) had significantly higher baseline tacrolimus trough levels despite receiving a lower initiation dose per kilogram of body weight. After 1 and 6‐months posttransplant, the higher BMI group were receiving a significantly lower tacrolimus dose relative to their body weight, with a significant negative correlation between body weight and tacrolimus/kg body weight. There was no adverse relationship evident between tacrolimus dosing or concentration and graft function. Conclusions: Our study showed that standard dosing of tacrolimus based on body weight in individuals who were obese did not adversely affect their tacrolimus concentrations or transplant function.